2018
DOI: 10.1182/blood-2018-07-863431
|View full text |Cite
|
Sign up to set email alerts
|

T-cell defects in patients with ARPC1B germline mutations account for combined immunodeficiency

Abstract: Abstract ARPC1B is a key factor for the assembly and maintenance of the ARP2/3 complex that is involved in actin branching from an existing filament. Germline biallelic mutations in ARPC1B have been recently described in 6 patients with clinical features of combined immunodeficiency (CID), whose neutrophils and platelets but not T lymphocytes were studied. We hypothesized that ARPC1B deficiency may also lead to cytoskeleton and functional defects in T cells. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 53 publications
4
91
0
Order By: Relevance
“…Nevertheless, our result is consistent with the recent study by Brigida et al ., which concluded that ARPC1B is also crucial for the Arp2/3 assembly and maintenance. They showed that alteration in the protein structure of ARPC1B hinders IS assembly . Together with our observations in bulk cytotoxicity assays, we propose that certain CTL functions as well as their adhesion to the target cells are facilitated by Arp2/3‐dependent cell morphology.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, our result is consistent with the recent study by Brigida et al ., which concluded that ARPC1B is also crucial for the Arp2/3 assembly and maintenance. They showed that alteration in the protein structure of ARPC1B hinders IS assembly . Together with our observations in bulk cytotoxicity assays, we propose that certain CTL functions as well as their adhesion to the target cells are facilitated by Arp2/3‐dependent cell morphology.…”
Section: Discussionsupporting
confidence: 80%
“…The formation of the IS could also be impaired, for example, as a result of the regulation of intracellular trafficking of organelles toward the immunological synapse. Approaches such as confocal imaging or rescue assays, which particularly enhance the TCR‐driven signaling machinery, can be used to further investigate this aspect …”
Section: Discussionmentioning
confidence: 99%
“…The first 6 diagnoses were obtained in a cohort of 32 patients. Three SCID/CID patients with mutations in RAG1, IL7R and ARPC1B genes [ (40,(45)(46)(47) and Volpi et al, under revision] were diagnosed in 8 T cell defects (37,5%). Moreover, JAGN1 (48), CECR1 (43) and NRAS genes, associated to complex phenotypes, were identified in 12 of the Other PIDs group (25%) (Figure 3C).…”
Section: Molecular Diagnosesmentioning
confidence: 99%
“…Loss-of-function mutations of ARPC1B give rise to multisystem inflammatory and immunodeficiency diseases (Brigida et al, 2018;Kahr et al, 2017;Kuijpers et al, 2017;Randzavola et al, 2019;Somech et al, 2017;Volpi et al, 2019), similar to Wiskott-Aldrich syndrome that is caused by mutations in the Arp2/3 activator WASP (Bosticardo et al, 2009). While some patients carry mutations causing premature protein termination and total loss of ARPC1B protein, four point mutations -W104S, A105V, V208F and A238T -have also been observed in patients (Brigida et al, 2018;Kahr et al, 2017;Volpi et al, 2019) (Figure 2A, right, purple spheres). W104, A105 and V208 are located in the core of the ARPC1B subunit β-propeller fold and this mutation likely destabilizes its tertiary fold, causing severely reduced protein levels in patients (Kahr et al, 2017).…”
Section: Isoform Specific Subunit Conformation and Determinants Of Acmentioning
confidence: 96%
“…Recent work has shown that the ARPC1 and ARPC5 isoforms differentially affect the actin nucleating properties of the Arp2/3 complex and the stability of the branched filament networks it generates (Abella et al, 2016). Furthermore, tissue-specific expression patterns of subunit isoforms, together with isoformspecific susceptibility to disease-causing point mutations, point to distinct physiological roles for particular Arp2/3 isoforms including cytotoxic T lymphocyte maintenance and activity (Brigida et al, 2018;Kahr et al, 2017;Kuijpers et al, 2017;Randzavola et al, 2019;Roman et al, 2017;Somech et al, 2017;Volpi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%